Designing a system for Online Orchestra: Computer hardware and software. Issue 2 (1st December 2017) - Prior, David; Biscoe, Ian; Rofe, Michael; Reuben, Federico
Online Orchestra sought in its pilot performance to enable musicians in four remote locations in Cornwall, United Kingdom, to make music together over the Internet. This article considers the processes by which computer hardware and software platforms were selected, integrated and optimized for the performance. Starting with an overview of guiding design principles, details of the computer hardware and software platforms used are provided. Audio- and video-streaming solutions are surveyed, leading to a detailed analysis of JackTrip and its deployment in the final system. The network environment in which the Online Orchestra performance took place is also considered, including specifications of each of the four venues.